URBAN WATERFRONT SUSTAINABLE MANAGEMENT WITHIN LIFE CYCLE ANALYSIS Case: South European Cities - Zulaikha Budi Astuti; Arif Kusumawanto; Wahyu Wilopo (ASEAN Journal of Systems Engineering, 2013)
This research develops a monitoring tool for urban plan-process based on Life Cycle Analysis by Lourenço. A special project of urban waterfront revitalization is proposed as a contribution to legitimize the LCA model. This research also proposes the influence and the success key factors of its behavior plan-process.The model is tested through benchmarking for six waterfront cities in South Europe. Bilbao in Spain, Genoa in Italy, and Lisbon in Portugal are considered as the success projects since the urban strategy has a strong link with the urban waterfront area notified by the high intensity of the cycle for each phase. Porto and Viana do Castelo in Portugal are considered as the success projects which have a similar behavior for the action and living phase which might be due to the same project under national policy and the projects touch economic and social opportunity of the people. Aveiro in Portugal shows rupture in the beginning, followed by high intensity in the next period which has similar behavior with ideal behavior of LCA model.This research shows the applicability of LCA Model to monitor waterfront revitalization projects and enables the discussion of conceptual issues related to the legitimizing of LCA and the present contribution. The behavior of urban waterfront area and the time dimension can be monitored and the influenced factors of the behavior can be noticed with the success key factors, those are: Planning: does the urban waterfront become the focus of the city planning? Action: does the project persistence in the design proposal? andLiving: does the urban waterfront touch social, culture and economic of the people activities?.